MODEL BIAYA OPERASI KENDARAAN PADA KAWASAN TRANSMIGRASI DI KABUPATEN ROKAN HULU - Pada Lumba (Universitas Pasir Pengaraian, 2013)
Generally the condition of roads at transmigration area in Rokan Hulu is still not on the asphalt, which indirectly this will affect accessibility to this area. This thing will make problems for road users, particularly related to vehicle operating cost.In this study, the researcher create a model of vehicle operating costs, especially for trucks. Where the vehicle is used by local residents for transporting farm crops in this area is to be brought to the factory. This model is influenced by the independent variable speed trucks.From the results obtained by the analysis of vehicle operating cost model trucks: fuel consumption model Y = 7,68E-6 V3 – 0,001 V2 + 0,032 V – 1,35 with R2 = 0.728 and the value of F = 5.361, lubricating oil consumption model Y = 4,62E-7 V3 – 5,6E-5 V2 + 0,002 V – 0,12 with R2 = 0.689 and the value of F = 4.431 and tire usage model Y = 5.46E-7 V + 9.72E-5 with a value of R2 value = 0.423 and F = 5.876